SISTEM PERENCANAAN PENYALURAN AIR BUANGAN DOMESTIK DI KECAMATAN TELANAIPURA KOTA JAMBI - Marhadi Marhadi; Robby Ikhsan (Jurnal Ilmiah Universitas Batanghari Jambi, 2015)
The planning of sewerage system  in Telanaipura subdistrict is an urgent program. This is because there are many puddles of water on the area that can interfere the the community. Therefore we need a domestic sewerage system that carried by by pipeline form the tank to the building septic processing (small bore sewer). For domestic wastewater treatment used sump wells equipped with pumps, initial sedimentation pond, stabilization pond, and collector pond. It is expected that delivery system and treatment of domestic waste water in the Telanaipura can reduce sanitation problems and the can realize a healthy region, comfortable and livable.Keyword : Telanaipura, small bore sewer, sewerage